MYANMAR MILITARY COUP 2021 IN INTERNATIONAL LAW: English - Puput Lutfiah; Amelia Suci Ramadhani; Daru Setyadharma Mardi Leksono; Syalaizha Febtria Putri Prasetya; Kintan Nabilah Saputra; Windy Nauli Sabbastine (International Journal of Law and Legal Ethics, 2023)
Nowadays, problems in a country can be related to internal and external problems. These problems are often not included in disputes or problems between international countries but can also be problems between one country and its internal ones that threaten order and peace in the international world. One example is the case of a coup where a process of overthrowing a key government is carried out by a certain group or party, while a military coup is carried out by a group of armed forces together with the state police with the emergence of acts of violence carried out by the military against civilians. Myanmar has a history of military coups from 1962, 1988 until 2021 but this case cannot be interfered with other countries, international or regional organizations because of binding international law, this creates a polemic for all parties.